Long-term outcome in patients with heart failure after cardiac surgery other than coronary artery bypass grafting treated with cardiac resynchronization therapy. (3rd October 2022) - Jedrzejczyk-Patej, E; Mazurek, M; Lenarczyk, R; Sokal, A; Kotalczyk, A; Kowalska, W; Gumprecht, J; Kowalski, O; Kalarus, Z
Abstract: Background: Cardiac resynchronization therapy (CRT) has been proven therapy in patients with heart failure (HF) and reduced left ventricular ejection fraction (LVEF). However, little is known about the prognosis, and the risk of cardiac device-related infective endocarditis (CDRIE) in patients with HF after cardiac surgery other than coronary artery bypass grafting (CABG) treated with CRT. Aim: To assess the long-term outcome, mortality predictors, and the risk of CDRIE in patients with HF after cardiac surgery other than CABG treated with CRT. Methods: The study population consisted of 1059 consecutive patients with CRT implanted between 2002 and 2019 in a tertiary care university hospital in a densely inhabited, urban region of Poland (949 subjects [89.6%] with CRT-D; 110 patients with CRT-P [10.4%]). Results: The studied population was divided into two groups according to be or not after cardiac surgery other than CABG (n=74 patients [6.9%] vs. n=985 patients [93.1%]). During the median follow-up of 1661 days (10th and 90th percentile: 323–3995), all-cause mortality in patients after cardiac surgery other than CABG did not differ significantly in comparison to other CRT recipients (50% vs. 54.4%, P=0.46). Also, the risk of CDRIE was not statistically significant differ (2.7% vs. 5.7%, P=0.28). On multivariable regression analysis, only older age (HR 1.04, 95% CI 1.01–1.07, P=0.02) was identified as independent predictor of higher mortality in patients after cardiac surgery treated with CRT. Kaplan-Meier curves of survival of patients after cardiac surgery other than CABG treated with cardiac resynchronization therapy in comparison to other CRT recipients are presented on Picture 1. Conclusions: The mortality rate in patients after cardiac surgery other than CABG is similar to other subjects treated with CRT and reaches 50% within 4.5 years. The risk of device-related infective endocarditis is not higher than in other patients treated with CRT. Advanced age is an independent mortality predictor in subjects after cardiac surgery other than CABG undergoing CRT. Funding Acknowledgement: Type of funding sources: None.